Validation of the Chinese version of the adverse life experiences scale - Zhao, Luowei; Li, Yuling; Wang, Zhilin; Wu, Jie (Frontiers in Pediatrics, 2024)
Background：Adverse childhood experiences (ACEs) are strongly linked to many mental health problems, and play important role in the intergenerational transmission of psychopathology. Additionally, the developmental timing may also be critical in ACEs' impact on these problems. The Adverse Life Experiences Scale(ALES), as a recently developed measure, has demonstrated good reliability and validity in indexing cumulative risk, developmental timing, and intergenerational transmission. This scale has not been used in China. The purpose of present study was to revise the Chinese version of the ALES and examine its psychometric properties.Methods: A total of 527 parents (fathers n=246, mothers n=281) from families with at least one child (12-18 years) completed this online survey. Internal consistency, test-retest reliability, correlations, regression models were examined for assessing the psychometric properties of the Chinese version of the ALES.The Chinese version of the ALES showed acceptable internal consistency (children: α = .72, parents: α = .74) and test-retest reliability (children: r = .86, parents: r = .84). In terms of validity, both parents and children's ACEs scores (total score and most age intervals scores) were significantly correlated with their current symptoms; ACEs scores of some age intervals in early childhood and adolescence significantly predicted symptoms in regression models; and parents' ACEs total score significantly correlated with children's ACEs total score and symptoms(all, girls, boys) except boys' Strengths and Difficulties Questionnaire total score.The Chinese version of the ALES showed good psychometric properties for assessing ACEs cumulative risk, developmental timing, and intergenerational transmission, and can serve as a reliable tool to evaluate ACEs in Chinese samples.